PERAN DAN WEWENANG KURATOR DALAM KEPAILITAN PERSEROAN TERBATAS - Rumelda Silalahi; Onan Purba (JURNAL RETENTUM, 2020)
A limited company that is declared bankrupt does not immediately stop and dissolve, but still exists as a legal entity. Under certain circumstances it can still run its business as usual. Limited companies do not occur bankruptcy fans can still run their business. This is because the limited liability company declared bankruptcy has an economic value that is much higher than the value of the company's assets. Because bankruptcy is actually intended for companies that have negative assets. However, the decision to continue the company goes bankrupt results in the power of the board of directors in a limited liability company. However, with the existence of a bankruptcy declaration, the debtor for the sake of law loses the right to control and manage his assets which are included in the bankruptcy estate as of the day of the decision on the bankruptcy statement. In the bankruptcy law, it is clearly stated that the curator is a Heritage Hall or a private person appointed by the court to manage and settle the assets of the bankrupt debtor under the supervision of the supervisory judge. In the event of a limited liability company bankruptcy, the curator has the obligation to be able to manage and settle all bankruptcy assets and keep all related documents.